The Incidence of Molluscum contagiosum among American Indians and Alaska Natives. - Mary G Reynolds (Public Library of Science (PLoS), 2009)
Background The epidemiology of Molluscum contagiosum (MC) in the United States is largely unknown, despite the fact that the virus is directly communicable and large outbreaks occur. This study provides population-based estimates to describe the epidemiology of MC in the United States among American Indian and Alaska Native (AI/AN) persons. This population was selected because of the comprehensiveness and quality of available data describing utilization of out-patient services. Principal findings Outpatient visits listing MC as a diagnosis in the Indian Health Service National Patient Information Reporting System during 2001-2005 were analyzed to assess patient characteristics, visit frequency and concurrent skin conditions. Outpatient visit rates and incidence rates were calculated based on known population denominators (retrospective cohort). Overall outpatient visit rates were also calculated for the general US population using national data. The average annual rate of MC-associated outpatient visits was 20.15/10,000 AI/AN persons for 2001-2005 (13,711 total visits), which was similar to the rate for the general US population (22.0/10,000 [95% CI: 16.9-27.1]). The incidence of MC-associated visits was 15.34/10,000. AI/AN children 1-4 years old had the highest incidence (77.12), more than twice that for children 5-14 years old (30.79); the incidence for infants (<1 year) was higher than that for adults. AI/AN persons living in the West region had the highest incidence, followed by those in the East and Alaska regions (26.96, 22.88 and 21.38, respectively). There were age-specific associations between MC and concurrent skin conditions (e.g., atopic dermatitis, eczema). Conclusions This study highlights the need for periodic population-based measurements to assess trends in incidence and healthcare utilization for MC in the United States. High rates of MC were found among AI/AN persons, especially among children <15 years old. The AI/AN population would benefit from greater availability of effective strategies for prevention and treatment of MCV infection.